Tanggung Jawab Pidana Korporasi Rumah Sakit - Hasrul Buamona (Jurnal Hukum Novelty, 2016)
Hospital is an institution that provides comprehensive health services on preventive, promotive, curative and rehabilitative to the public at largeas regulated in Article 1 (3) of Law Number 44 Year 2009 About the Hospital, which says "Comprehensive health services are health services which include promotive, preventive, curative, and rehabilitative services. In addition, the hospital is an institution that dense of capital, technology and human resources, so it could potentially cause problems both internally and externally. The hospital previously regarded as a social institution that provides medical assistance to the public, but in the present position of the hospital has experienced changes, which had shaped a social institution become an institution in the form of a corporation incorporated under the law which have the rights and obligations as a legal person (rechts persoon) that lead to a dominant profit-seeking health services. Issues that have sprung up in the present, in case of medical errors by physicians or health workers who work in hospitals and provide economic or moral benefits, patients litigate doctors, especially criminal law, and never asked the corporate criminal liability of hospital that the establishment has a legal entity (rechts persoon). That issue makes the writer interested in reviewing whether the hospital as a corporation can be held criminally liable. The result of this study showed that the hospital can be held criminally liable because a hospital as a corporation is a legal person (rechts persoon) who have rights and obligations as well as a natural person (naturlijke persoon). Besides, the legal doctrine of Vicarious Liability and Strict Liability hold that there can be a person liable for the actions of his employees as far as the employment relationship in a hospital/corporation.